The Personality Structure of Ella Marchmill in "An Imaginative Woman" by Thomas Hardy: A Study of Freud's Psychology - Sitti Hardianti; Yusniati N. Sabata (BABASAL English Education Journal, 2023)
The purpose of this study is to find and analyze the aspects of personality structure (id, ego, superego) in Ella Marchmill's characters, as well as the conflicts and personality structures that dominate. An Imaginative woman is a short story that tells how a household relationship in the Victorian era, especially how the personality structure of a wife in that era, was described by Thomas Hardly in the main character Ella Marchmill. The theory that will be used regarding personality structures (Id, Ego, Super Ego) by Sigmund Freud. Then, the method used is a descriptive qualitative research method by analyzing data in the form of words, phrases, dialogues, etc. from Ella Marchmill’s caharacters in An Imaginative Woman. This method was chosen because it’s relevant with the problems and the data is from data which is a words, dialogues, etc to be analyzed, not a mathematical problem. The results of the study prove that: 1) Ella Marchmill's character has three personality structures, they are id, ego, and superego. 2) The inner conflict that Ella Marchmill has an impact on the dominance of her personality structure, id. Ella always tries to have the object of her id (pleasure principle), namely Mr. Trewe even though she had to break the superego (rules) that existed as a woman in the Victorian era by betraying her own husband.